Dewey Bob - Schachner, Judith Byron (New York, NY : Dial Books for Young Readers, 2015)
Dewey Bob Crockett is a young raccoon who loves to collect shiny things, but he discovers that it is a lot harder for a raccoon to collect--and keep--a friend.
Keywords: Raccoon -- Juvenile fiction; Friendship -- Juvenile fiction; Collectors and collecting -- Juvenile fiction; Raccoon -- Fiction; Friendship -- Fiction; Collectors and collecting -- Fiction